1996
DOI: 10.1046/j.1525-1438.1996.06060483.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of p53 mutation and over-expression in ovarian cancer prognosis

Abstract: Mutation of the p53 tumor suppressor gene is the most commonly observed genetic abnormality in human tumors and associations between p53 aberration and patient survival have been shown for several tumor types. Previous studies have found that approximately 50% of epithelial ovarian carcinomas exhibit abnormalities in the p53 gene. The aim of this study, therefore, was to examine the potential prognostic significance of aberrant p53 in patients with primary epithelial ovarian carcinoma. Using immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
(8 reference statements)
4
14
0
Order By: Relevance
“…In agreement with earlier reports [19,31,32], our studies showed no significant association between histological grade and p53 overexpression. However, others have shown that p53 aberrations were correlated with poor tumor differentiation [11,12,16,35,39,41]. Similar to our previous observations, a large volume of published data [17,32,35,38,39] indicates that carcinomas showing p53 changes are usually classified as III/IV FIGO stages.…”
Section: P53 Overexpression P53 Mutations and Response To Cisplatin-supporting
confidence: 89%
See 2 more Smart Citations
“…In agreement with earlier reports [19,31,32], our studies showed no significant association between histological grade and p53 overexpression. However, others have shown that p53 aberrations were correlated with poor tumor differentiation [11,12,16,35,39,41]. Similar to our previous observations, a large volume of published data [17,32,35,38,39] indicates that carcinomas showing p53 changes are usually classified as III/IV FIGO stages.…”
Section: P53 Overexpression P53 Mutations and Response To Cisplatin-supporting
confidence: 89%
“…However, others have shown that p53 aberrations were correlated with poor tumor differentiation [11,12,16,35,39,41]. Similar to our previous observations, a large volume of published data [17,32,35,38,39] indicates that carcinomas showing p53 changes are usually classified as III/IV FIGO stages. Nevertheless, others have been unable to show such relationships [16,19,31,36,40,41].…”
Section: P53 Overexpression P53 Mutations and Response To Cisplatin-supporting
confidence: 89%
See 1 more Smart Citation
“…For p53, 62 studies reporting results of 75 analyses in 9448 patients were included (Supplementary Table 3; median study size 102 patients, range 20-783; Hartmann et al, 1994;Klemi et al, 1995;Allan et al, 1996;Eltabbakh et al, 1997;Viale et al, 1997;Darai et al, 1998;Marx et al, 1998;Silvestrini et al, 1998;Anttila et al, 1999;Baekelandt et al, 1999;Kassim et al, 1999;Wen et al, 1999 ). There were 13 prospective studies and 49 retrospective studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Mutations of the p53 gene as determined by mutation analysis and/or positive immunohistochemical (IHC) staining for p53 are common in ovarian cancer and have been associated with poor clinical outcome. However, results of the many studies on the prognostic value of p53 expression in ovarian cancer are inconclusive (Marks et al, 1991;Hartmann et al, 1994;Van Der Zee et al, 1995;Allan et al, 1996;Anttila et al, 1999;Ferrandina et al, 1999;Reles et al, 2001;Nakayama et al, 2003;Nielsen et al, 2004). One of the most important reasons for these conflicting results is the considerable methodological variability among the different studies (Hall et al, 2004).…”
mentioning
confidence: 99%